2010
DOI: 10.1093/intqhc/mzq049
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a nationwide outreach program on the diffusion of evidence-based practice in Taiwan

Abstract: The knowledge of, skill in, and behavior regarding EBP have improved among physicians and nurses of regional hospitals in Taiwan after a promotion period of 2 years and they perceive fewer barriers to EBP. These data suggest that the multifaceted nationwide promotion program of the type conducted by NHRI succeeded in diffusion and implementation of EBP among professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 25 publications
1
29
0
Order By: Relevance
“…30 To optimize the response rate we used a cluster sampling, which improves response rate, compared to random sampling. 31 Third, our sample size was small. Nevertheless, our study is the pioneer in evaluating the EBP profile of RTs.…”
Section: Discussionmentioning
confidence: 97%
“…30 To optimize the response rate we used a cluster sampling, which improves response rate, compared to random sampling. 31 Third, our sample size was small. Nevertheless, our study is the pioneer in evaluating the EBP profile of RTs.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, gender was a factor related to dissemination. However, this factor is profession related21: male physicians are more common (92.3%) than male librarians (14.3%).…”
Section: Discussionmentioning
confidence: 99%
“…Third, mentoring relationships, such as support from early adopters and designated personnel, can enhance dissemination 12. Fourth, education and training can increase knowledge of and skill in how to access and further maximise levels of self-sufficiency in its efficient use 21. For example, academic detailing by early adopters has proven valuable for changing behaviour 22…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…27,28 The study in Taiwan reported that an outreach program offering evidence-based practice (EBP) learning resulted in the increased knowledge, gained positive attitudes, and increased perceived skills in the application of EBP among nurses, whereas overall the program had a greater impact on physicians. 29 Under the banner of EBM, CPGs are characterized as objective, uniform, and efficient in healthcare; conversely, the use of CPGs may threaten the establishment of professional autonomy and the professional's role. 27,28 Safe handling guidelines for chemotherapy have been available for more than 3 decades.…”
mentioning
confidence: 99%